Cryopreservation of adipose tissue-derived mesenchymal stem cells: An alternative to serial fat grafting in breast reconstruction - Marcelo Moreno; Eloisa Lehr Filippi Chiella; Raphaela Passuello; Aline Manica; Juliana Cristina Schmidt (Revista Brasileira de Cirurgia Plástica)
Introduction: Fat grafting is an autologous graft of cells from subcutaneous tissue, which can be used as a complementary technique in breast reconstruction. Given this, the cryopreservation of adipose tissue-derived mesenchymal stem cells (ADMSCs) could be a way to collect them in one surgical procedure and after performing fractional fat grafting. Dimethyl sulfoxide (DMSO) is a cryopreservative used in cell research, but it is potentially toxic, which would make it impossible to use cryopreserved ADMSCs in clinical practice. New cellular cryopreservatives, without toxicity, have been described in the experimental scientific literature, such as the substances L-proline and trehalose. Therefore, this work aimed to evaluate the viability of ADMSCs cryopreserved with the combination of L-proline and trehalose over up to 90 days. Method: Experimental study in which lipoaspirate samples were obtained from 9 patients. The cellular fraction was processed and frozen with L-proline (1.5M) + trehalose (0.2M) or with DMSO + fetal bovine serum (FBS) as control. After 30 and 90 days, the samples were thawed, and cell viability was assessed using the MTT technique. Results: The analysis of ADMSCs, after 1 and 3 months of freezing, indicated that samples treated with L-proline + trehalose showed similar viability to those preserved with DMSO and SFB (p=0.444). Conclusion: The association of L-proline and trehalose kept ADMSC viable for 30 and 90 days of freezing, and could be an alternative as a cellular cryopreservative without toxicity and enabling the use of serial fat grafting.